Effect of N2 on release behavior of D2 in liquid lithium. (September 2021) - Li, L.; Zhang, D.H.; Meng, X.C.; Yuan, J.S.; Huang, M.; Zuo, G.Z.; Hu, J.S.
Highlights: Nitrogen in liquid lithium has a significant effect on the desorption temperature of hydrogen isotopes. Chemical reactions and the formation of new D/N phases were suggested. The results may have a potential impact on tritium exaction in liquid lithium in future application. Abstract: Lithium is chemically active and prone to react with residual gases in the atmosphere, which should be taken into account for the application of lithium in fusion facility. In the present study, effect of N2 on the release temperature of D2 in liquid lithium was investigated. Absorption experiments were performed at 400 °C by exposing lithium in N2 or D2 atmosphere. Thermal desorption spectrometry (TDS) was used to measure the desorption temperature of Li samples. New D2 peaks which are below the decomposition temperature of LiD but higher than that of D2 dissolved in liquid lithium are observed in Li samples that have absorbed both D2 and N2 and the desorption temperature of which varies according to the ratio of N2 and D2 . Although the mechanism of this reaction is not clear, these results highlight the importance of monitoring the impurity content of liquid lithium and the potential impact on tritium extraction when lithium is applied in fusion facilities.